До питання про типологію стилістичних засобів при перекладі рекламних текстів - Косенко, А.В.; Беженар, I. В.; Боднар, О.І. (My University, 2026)
The article is devoted to the analysis of stylistic techniques for reproducing advertising texts in translation. Based on the analysis of advertising slogans, several main structural types of advertising constructions are distinguished: 1. binary constructions, in which the brand is combined with an explanatory or emotional part through a colon, period or other punctuation marker. Binary constructions include the following subgroups: informativeidentifying constructions, explanatory-logical constructions, emotional-figurative constructions, evaluative-motivational constructions. Monopart constructions that constitute a full-fledged independent sentence - imperative, infinitive, parallel or elliptical; aphoristic (nominative) constructions, which are characterized by a noun or prepositional construction and semantic completeness despite the absence of a verbal predicate. We also identified the following types of transformations in the translation of stylistic means of advertising slogans: lexical transformations: differentiation transformation; deletion transformation; addition transformation; concretization transformation. Grammatical transformations: grammatical replacement transformation; transposition (permutation) transformation. Lexicogrammatical transformations: structural restructuring transformation; modulation transformation, descriptive translation and antonymic translation. According to the results of statistical analysis, the following quantitative indicators were obtained: the most used was the structural restructuring transformation, which indicates the need for a deep adaptation of the content of advertising slogans to the norms of the Ukrainian language and cultural context. The second most frequent transformation was the transposition transformation, which indicates the importance of rearranging the word order to achieve naturalness and melodiousness of the Ukrainian expression. The third place is occupied by the grammatical replacement transformation, which demonstrates a tendency to adapt the grammatical structures of the English language in accordance with the norms of Ukrainian syntax. The results obtained demonstrate that the translation of advertising slogans requires a comprehensive approach combining several transformations, among which structural restructuring, transposition, and grammatical substitution play a leading role.
Keywords: intercultural advertising communication, advertising discourse, advertising communication, linguostylistics, translation, translation strategy.